Recent Advances in Cellular Signaling Interplay between Redox Metabolism and Autophagy Modulation in Cancer: An Overview of Molecular Mechanisms and Therapeutic Interventions - Md. Ataur Rahman; Kazi Rejvee Ahmed; Farzana Haque; Moon Nyeo Park; Bonglee Kim (MDPI AG, 2023)
Autophagy is a fundamental homeostatic process in which certain cellular components are ingested by double-membrane autophagosomes and then degraded to create energy or to maintain cellular homeostasis and survival. It is typically observed in nutrient-deprived cells as a survival mechanism. However, it has also been identified as a crucial process in maintaining cellular homeostasis and disease progression. Normal cellular metabolism produces reactive oxygen (ROS) and nitrogen species at low levels. However, increased production causes oxidative stress, which can lead to diabetes, cardiovascular diseases, neurological disorders, and cancer. It was recently shown that maintaining redox equilibrium via autophagy is critical for cellular responses to oxidative stress. However, little is understood about the molecular cancer processes that connect to the control of autophagy. In cancer cells, oncogenic mutations, carcinogens, and metabolic reprogramming cause increased ROS generation and oxidative stress. Recent studies have suggested that increased ROS generation activates survival pathways that promote cancer development and metastasis. Moreover, the relationship between metabolic programming and ROS in cancer cells is involved in redox homeostasis and the malignant phenotype. Currently, while the signaling events governing autophagy and how redox homeostasis affects signaling cascades are well understood, very little is known about molecular events related to autophagy. In this review, we focus on current knowledge about autophagy modulation and the role of redox metabolism to further the knowledge of oxidative stress and disease progression in cancer regulation. Therefore, this review focuses on understanding how oxidation/reduction events fine-tune autophagy to help understand how oxidative stress and autophagy govern cancer, either as processes leading to cell death or as survival strategies for maintaining redox homeostasis in cancer.